From the Observatory for Monitoring Corruption and Professional Ethics in the Democratic Republic of Congo: the secular arm of the rule of law - GAYO BULAMBO Cadet (International Journal of Scientific Research and Innovative Studies, 2026)
This article analyses the legal and institutional role of the Observatory for Monitoring Corruption and Professional Ethics (OSCEP) in consolidating the rule of law in the Democratic Republic of Congo. Initially established as a public service responsible for promoting the Code of Conduct for Public Officials, the OSCEP was transformed into a technical public institution in order to strengthen its prerogatives, particularly in the prevention, detection and punishment of corruption and anti-values in socio-professional circles. The study highlights a persistent gap between the formal scope of the OSCEP's statutory powers and its actual operational effectiveness. Through a teleological and systemic analysis of the applicable legal texts, supplemented by direct observation and interviews with the institution's agents, the article identifies the structural and functional causes of this dysfunction, which include weak institutional autonomy, insufficient internal scientific research, shortcomings in merit-based recruitment mechanisms, and the inertia of the judicial police function recognised by the OSCEP. In conclusion, the author argues that revitalising the OSCEP requires targeted legal and institutional reforms, including effectively attaching it to the Prime Minister's Office, strengthening its financial autonomy, establishing binding ethical consultation mechanisms, and adapting the national procedural framework to international standards on combating corruption. The OSCEP is thus seen as a strategic instrument that is still under-exploited for strengthening ethical governance and the rule of law in the DRC. Keywords: OSCEP, corruption, professional ethics, governance, prevention, autonomy, supervision, anti-values, Judicial Police Officer, Practical Effectiveness, institutional reform. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/567